2012
DOI: 10.1111/jam.12064
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and virulence profiles of atypical enteropathogenic Escherichia coli (EPEC) isolated from bovine farms and abattoirs

Abstract: Aims: The objective of this study was to examine the prevalence of enteropathogenic Escherichia coli (EPEC) on beef and dairy farms and in beef abattoirs and to characterize the isolates in terms of serogroup and virulence markers. Methods and Results: Bovine faecal samples (n = 1200), farm soil samples (n = 600), hide samples (n = 450) and carcass samples (n = 450) were collected from 20 farms and three abattoirs throughout Ireland over a 12-month period. After selective enrichment, samples testing positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
(89 reference statements)
3
20
1
4
Order By: Relevance
“…Globally, there are various studies showing that aEPEC has different serogrous, such as O76 (Møller-Stray et al, 2012), O127 (Hao et al, 2012), O119, O26, and O88 (Jenkins et al, 2003). In this study, 7.4% of aEPEC isolates were O untypable, which is much lower than that reported by others (Blanco et al, 2006; Monaghan et al, 2013; Zhang et al, 2016). Blanco et al found that 110 EPEC strains were typed to 43 O serogroups and 69 serotypes with 44 new serotypes and only 13% could be assigned to classical EPEC serotypes (Blanco et al, 2006).…”
Section: Discussioncontrasting
confidence: 72%
“…Globally, there are various studies showing that aEPEC has different serogrous, such as O76 (Møller-Stray et al, 2012), O127 (Hao et al, 2012), O119, O26, and O88 (Jenkins et al, 2003). In this study, 7.4% of aEPEC isolates were O untypable, which is much lower than that reported by others (Blanco et al, 2006; Monaghan et al, 2013; Zhang et al, 2016). Blanco et al found that 110 EPEC strains were typed to 43 O serogroups and 69 serotypes with 44 new serotypes and only 13% could be assigned to classical EPEC serotypes (Blanco et al, 2006).…”
Section: Discussioncontrasting
confidence: 72%
“…Seventeen epidemiologically important variants of intimin have been reported (Blanco et al, 2005). The EPEC/ETEC strain found to carry intimin-␤ type, which was common among the aEPEC isolated from Peruvian children, diarrheal patients from Japan (Contreras et al, 2012;Wang et al, 2013) and also in bovine farms and abattoirs in Ireland (Monaghan et al, 2013). These aEPEC strains of animal origin possess essential virulence machinery to cause infection in humans also (Monaghan et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of the verotoxin genes was evaluated as previously described (21,22). Briefly, 1-ml samples of TSB cultures, grown overnight, were pelleted, and genomic DNA was extracted using the DNeasy tissue kit (Qiagen, Crawley, United Kingdom) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 1-ml samples of TSB cultures, grown overnight, were pelleted, and genomic DNA was extracted using the DNeasy tissue kit (Qiagen, Crawley, United Kingdom) according to the manufacturer's instructions. DNA was screened for the presence of stx 1 and/or stx 2 genes by PCR (Peltier thermal cycler [PTC-200]) using the primers and conditions previously reported (21,22). PCR products were separated by electrophoresis on a 1.5% (wt/vol) agarose gel and visualized under UV light (GelDoc 2000 system; Bio-Rad Laboratories, Hercules, CA) by ethidium bromide staining (10 mg/ml).…”
Section: Methodsmentioning
confidence: 99%